Origin of Tasawwuf (Sufism) and Critiquing The Thesis of Transition from Zuhd - Mohamed Meerasahibu, Dheen Mohamed (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The origins of tasawwuf have long been a subject of debate in scholarly circles, with prevailing views suggesting that it emerged as a later development influenced by the concept of zuhd. This article challenges this commonly held view, arguing that such assertions are rooted in a superficial reading of Islamic sources and the earlier literature on tasawwuf. By probing deeper into the original sources and the accounts of classical Sufi masters, this article seeks to demonstrate that tasawwuf cannot simply be regarded as a transitional stage from zuhd, influenced by various internal and/or external factors. Instead, it is an integral part of the religion of Islam, embodied in the notion of ihsan, which is the spiritual ideal of Islamic faith and practice. In its discussion, the article will briefly touch upon what the author believes to be the factors that have led to the misreading and misrepresentation of the history of tasawwuf in both Western and many Muslim writings. Departures from unchecked preconceived notions, and the use of Western concepts and categorizations—belonging to a different cultural context—in studying tasawwuf are identified as some of these factors. By relying on original sources and employing a historical-critical method, this paper aims to clarify that tasawwuf is, in essence, the art of realizing ihsan in theory and practice. As such, it originated with Islam, though its nomenclature and organizational structures may have developed later.